In vitro antimicrobial and cytotoxic activity of Tamarix dioica Roxb. leaves - Khan, Saifullah; Ullah, Farman; Mahmood, Tahir (TUBITAK Scientific & Technical Research Council Turkey, 2013)

(untitled)
Medicinal plants have been in use for thousands of years for treatment of different types of diseases and a large inventory of useful drugs has been isolated from them. The aim of our study is to investigate a new and effective plant possessing antimicrobial activity. The crude extracts of Tamarix dioica Roxb. leaves, as well as fractions of the extract in various solvents, were investigated against standard strains of bacteria Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae, Shigella flexneri, Bacillus subtilis, Salmonella typhi, and Staphylococcus aureus and fungi Candida glabrata, Aspergillus niger, Trichophyton rubrum, Candida tropicalis, and Aspergillus fumigatus. For in vitro antibacterial and antifungal studies of T. dioica extracts, the agar well diffusion technique was used. For cytotoxic study, brine shrimp (Artemia salina) larvae were used. Results of the crude extract and some fractionated samples showed significant antifungal properties, but low antibacterial response and negligible cytotoxic activity. It was recognized that Tamarix dioica has the potential for future development of new antifungal drugs/medicine.